Leading and Emerging Sectors for Regional Development Planning: A Multi-Method GRDP Analysis - Budiyansa; Patta Tope; Yunus Sading (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study examines regional economic structure during the 2015–2024 period using a multi-method regional analysis framework. Gross Regional Domestic Product (GRDP) data at constant prices were analyzed across 17 economic sectors, with the provincial economy serving as the reference region. The methods applied include Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift-Share Analysis focusing on the competitive share component, Klassen Typology, and Relative Sectoral Productivity (RPs). The study aims to identify leading and emerging sectors to support evidence-based regional development planning. The findings reveal a structural transformation characterized by declining competitiveness in traditional sectors such as agriculture and manufacturing, while new growth trajectories are emerging in information and communication, financial services, construction, and education. The integration of five analytical methods enables the classification of sectors into three policy priority groups: leading and sustainable sectors, emerging and scalable sectors, and declining sectors requiring revitalization. This classification provides a robust empirical basis for differentiated regional development strategies. The study recommends targeted policy interventions to strengthen high-performing sectors, accelerate promising sectors, and revitalize structurally lagging sectors